Efficient Removal of Ammonia by Hierarchically Porous Carbons from a CO2 Capture Process. Issue 10 (9th September 2020) - Choi, Jeong Ho; Jang, Jong Tak; Yun, Soung Hee; Jo, Won Hee; Lim, Seong Seon; Park, Joung Ho; Chun, Il Soo; Lee, Jung-Hyun; Yoon, Yeo Il
Abstract: The amine‐based post‐combustion carbon capture process is one of the most efficient methods for treating large‐scale CO2, but it produces hazardous products due to chemical transition and degradation of the absorbents. In this study, carbon‐based materials were used as adsorbents for the removal of NH3, and their adsorption capacities, adsorption rates, and stabilities were examined by comparing commercial activated carbon (AC) with hierarchically porous carbon (HPC). HPC‐Step4 possessed a higher number of total acid sites, resulting in higher NH3 adsorption compared to AC. Despite the similar porosity, HPC‐Step4 exhibited a higher adsorption rate constant and the improved kinetics was attributed to its increased portion of mesopores, enhancing the diffusion rate of the adsorbate. Furthermore, HPC‐Step4 exhibited better reaction stability than AC. Abstract : Activated carbon (AC) and hierarchically porous carbon (HPC) preparations were used as adsorbents for the removal of NH3 after an amine‐based post‐combustion carbon capture process, and their adsorption capacities, adsorption rates, and stabilities were studied. In general, the HPC adsorbents with more mesopores and acid sites showed better performance and stability than the AC ones.